Instituições Federais de Ensino Superior como instrumento de política pública de inclusão social sob o viés constitucional: o caso da Universidade Federal de Goiás - Cruvinel, Pedro Henrique Moreira (2020)
Higher education in Brazil at the time of the Colony was aimed at elites. Unlike Spanish America, Brazil had no University as a Colony of Portugal. Thus, an elite from the colonial era formed in Coimbra together with a metropolitan elite, sharing the same habitus, which reinforced the Portuguese Empire unity. French sociologist Pierre Bourdieu explains how habitus influences an interaction of the individual-duo in the social field, in addition to revealing the means of domination existing in each social field, a domination that uses symbolic violence. In this sense, the Brazilian University, especially as Federal Institutions of Higher Education, is evaluated as spaces in which the subjects establish different interactions, each with their own interests. Thus, because they have autonomy, as IFES they ended up developing inclusive public policies, with a modifier to change their elitist profile. This time, the Federal University of Goiás (UFG) will serve as a paradigm to assess whether such policies were able to change their habitus.